Modeling how eutrophication in northern Baltic coastal zone is driven by new nutrient inputs, internal loading, and 3D hydrodynamics - Risto Lignell; Elina Miettunen; Harri Kuosa; Janne Ropponen; Laura Tuomi; Irma Puttonen; Kaarina Lukkari; Marie Korppoo; Markus Huttunen; Karel Kaurila; Jarno Vanhatalo; Frede Thingstad (Journal of Marine Systems, 2025)

Reproducing the virus‐to‐copepod link in Arctic mesocosms using host fitness optimization - T. Frede Thingstad; Selina Våge; Gunnar Bratbak; Jorun Egge; Aud Larsen; Jens Christian Nejstgaard; Ruth‐Anne Sandaa (Limnology and Oceanography, 2021)
By shunting material out of the predatory pathway toward detritus and dissolved material, viruses are believed to have an important impact on biogeochemical functions of the pelagic microbial food web. To include viruses as a single plankton functional type (PFT) in dynamic food web models is, however, not trivial since they will then compete with predators for the same host/prey community as a shared limiting resource. As recently shown, one can solve this problem by introducing adaptation in the defensive and competitive traits of the host (prey) community. We here show how this can reproduce central aspects of viral dynamics as observed in a set of Arctic mesocosm experiments. In these experiments, contrasting microbial trophodynamics have previously been linked to the trophic cascades generated by seasonal vertical migration of large Arctic copepods. This approach thus produces a quantitative theory for the mechanisms regulating virus‐to‐prokaryote and lysis‐to‐predation ratios, and integrates this with a central role of predator top‐down control in pelagic microbial food webs.

Simple models combining competition, defence and resource availability have broad implications in pelagic microbial food webs - Selina Våge; Gunnar Bratbak; Jorun Egge; Mikal Heldal; Aud Larsen; Svein Norland; Maria Lund Paulsen; Bernadette Pree; Ruth‐Anne Sandaa; Evy Foss Skjoldal; Tatiana M. Tsagaraki; Lise Øvreås; et al. (Ecology Letters, 2018)
In food webs, interactions between competition and defence control the partitioning of limiting resources. As a result, simple models of these interactions contain links between biogeochemistry, diversity, food web structure and ecosystem function. Working at hierarchical levels, these mechanisms also produce self‐similarity and therefore suggest how complexity can be generated from repeated application of simple underlying principles. Reviewing theoretical and experimental literature relevant to the marine photic zone, we argue that there is a wide spectrum of phenomena, including single cell activity of prokaryotes, microbial biodiversity at different levels of resolution, ecosystem functioning, regional biogeochemical features and evolution at different timescales; that all can be understood as variations over a common principle, summarised in what has been termed the ‘Killing‐the‐Winner’ (KtW) motif. Considering food webs as assemblages of such motifs may thus allow for a more integrated approach to aquatic microbial ecology.

Dampened copepod‐mediated trophic cascades in a microzooplankton‐dominated microbial food web: A mesocosm study - Bernadette Pree; Aud Larsen; Jorun Karin Egge; Paolo Simonelli; Rakhesh Madhusoodhanan; Tatiana Margo Tsagaraki; Selina Våge; Svein Rune Erga; Gunnar Bratbak; T. Frede Thingstad (Limnology and Oceanography, 2017)
Interactions of bottom‐up factors such as the availability of mineral and organic nutrients, and top‐down factors like predation and viral infection affect microbial communities of the pelagic food web. Hypothesis derived from previous experimental and modeling work suggest some general mechanisms on how these factors may be linked and call for an experiment to test interactions between (1) nitrogen source and diatom cell size, (2) bacterial growth rate limitation by mineral nutrients versus organic carbon, and (3) enhanced versus decreased predation pressure by copepods ( Calanus finmarchicus ). We performed a mesocosm experiment using a replicated three factor––two level full factorial design ( / , +/− glucose, and +/− copepods). Diatoms, pico‐ and nano‐sized autotrophs, prokaryotes, heterotrophic nanoflagellates, micro‐ and mesozooplankton abundances were monitored for 19 days. The main finding was a system that responded remarkably little to these manipulations with no effects of nitrogen source and only moderate effects of carbon treatments. Zooplankton manipulations had the strongest impact on microbial communities, but, opposite to our hypothesis based on previous studies, microzooplankton and diatoms increased during the first 7–10 days when mesozooplankton abundances were experimentally enhanced. We suggest that high abundances of dinoflagellates and ciliates and occurrence of rotifers, which dominated microzooplankton community in the first half of the experiment complicated trophic linkages between copepods, microzooplankton and diatoms. Apart from this dampened copepod mediated trophic cascade, we found tight couplings between communities of the microbial food web, with maxima of predator communities coinciding with low abundances of prey communities.

Micromonas versus virus: New experimental insights challenge viral impact - Eliana Ruiz; Anne‐Claire Baudoux; Nathalie Simon; Ruth‐Anne Sandaa; T. Frede Thingstad; António Pagarete (Environmental Microbiology, 2017)
Summary Viruses have recurrently been hypothesized as instrumental in driving microbial population diversity. Nonetheless, viral mediated co‐existence of r/k‐strategists, predicted in the Killing‐the‐Winner (KtW) hypothesis, remains controversial and demands empirical evidence. Therefore, we measured the life strategy parameters that characterize the relevant system Micromonas ‐Micromonas Virus (MicV). A large number of host and viral strains (37 and 17, respectively) were used in a total of 629 cross‐infectivity tests. Algal and viral abundances were monitored by flow cytometry and used to calculate values of growth rate, resistance capacity, and viral production. Two main assumptions of the KtW model, namely (1) a resistance‐associated cost on growth and (2) a negative correlation between resistance and viral production capacity, were mildly observed and lacked statistical significance. Micromonas strains infected by more MicV strains presented higher lysis and viral production rates as the number of infectious virus strains increased, suggesting a ‘one‐gate’ regulation of infection in this system. MicV strains demonstrated a vast range of virion production capacity, which unexpectedly grew with increasing host‐range. Overall, the significant trends observed in here demonstrate strong co‐interactions at different levels between Micromonas and MicV populations, however, the role of viruses as major driving force in phytoplankton fitness wasn't explicitly observed.

Linking internal and external bacterial community control gives mechanistic framework for pelagic virus‐to‐bacteria ratios - Selina Våge; Bernadette Pree; T. Frede Thingstad (Environmental Microbiology, 2016)
Summary For more than 25 years, virus‐to‐bacteria ratios (VBR) have been measured and interpreted as indicators of the importance of viruses in aquatic ecosystems, yet a generally accepted theory for understanding mechanisms controlling VBR is still lacking. Assuming that the denominator (total bacterial abundance) is primarily predator controlled, while viral lysis compensates for host growth rates exceeding this grazing loss, the numerator (viral abundance) reflects activity differences between prokaryotic hosts. VBR is then a ratio between mechanisms generating structure within the bacterial community and interactions between different plankton functional types controlling bacterial community size. We here show how these arguments can be formalized by combining a recently published model for co‐evolutionary host‐virus interactions, with a previously published “minimum” model for the microbial food web. The result is a framework where viral lysis links bacterial diversity to microbial food web structure and function, creating relationships between different levels of organization that are strongly modified by organism‐level properties such as cost of resistance.

Contrasting response to nutrient manipulation in A rctic mesocosms are reproduced by a minimum microbial food web model - Aud Larsen; Jorun K. Egge; Jens C. Nejstgaard; Iole Di Capua; Runar Thyrhaug; Gunnar Bratbak; T. Frede Thingstad (Limnology and Oceanography, 2015)

Successful strategies in size structured mixotrophic food webs - Selina Våge; Marco Castellani; Jarl Giske; T. Frede Thingstad (Aquatic Ecology, 2013)

Adding a cost of resistance description extends the ability of virus–host model to explain observed patterns in structure and function of pelagic microbial communities - Selina Våge; Julia E. Storesund; T. Frede Thingstad (Environmental Microbiology, 2013)
Summary By adding a generic description of cost of resistance ( COR ) to the existing ‘killing‐the‐winner’ model, we show how this expands the model's explanatory power to include rank‐abundance relationships in the host population. The model can predict a counter‐intuitive relationship previously suggested in the literature, where abundant viruses are associated with rare hosts and vice versa . The model explains the observed dominance of slow‐growing prokaryotes as the result of successful defence strategies, rather than as dormancy of hosts lacking essential substrates. In addition to these important conceptual aspects, the model is able to reproduce realistic values for virus : host ratios and partitioning of bacterial production between predatory loss and viral lysis. A high COR is also shown to increase the community's richness and S hannon diversity index. This model thus not only couples life strategies at the cellular level with system properties, but it also links the two system level properties of biogeochemical flows and diversity to each other. The model operates with host groups, and consequences for biodiversity when interpreting these groups in terms of species and strains are discussed.

Getting the “right” parameter values for models of the pelagic microbial food web - Risto Lignell; Heikki Haario; Marko Laine; T. Frede Thingstad (Limnology and Oceanography, 2013)
The microbial part of the pelagic food web is believed to be a highly dynamic and tightly coupled network in which system behavior emerges from organism properties and interactions. A central goal in microbial ecology is a quantitative understanding of these interactions. A key aspect of these linkages is again the efficiency of food acquisition in the different groups of planktonic organisms. Here we estimate osmotrophic nutrient affinity for inorganic nitrogen and phagotrophic prey clearance values, using a parsimonious model of the microbial food web and modern Bayesian Markov chain Monte Carlo (MCMC) methods. The model is fitted to experimental data from five mesocosms filled with northern Baltic seawater containing an N‐limited summer community and perturbed with different nutrient additions. The MCMC method successfully found one common set of parameters that not only gave a good fit to perturbation responses in all five mesocosms, but also was in reasonable agreement, both with values derived theoretically from first principles and allometric relationships, and with affinity values for phosphate in the experimental literature. Key properties of the structure and functioning of the microbial plankton food web can thus be derived and understood from fundamental physical‐chemical laws governing affinity for nutrient uptake by osmotrophs, and size‐selective grazing by key functional groups of phagotrophs.

Bacterioplankton groups involved in the uptake of phosphate and dissolved organic phosphorus in a mesocosm experiment with P‐starved Mediterranean waters - Marta Sebastián; Paraskevi Pitta; José M. González; T. Frede Thingstad; Josep M. Gasol (Environmental Microbiology, 2012)
Summary The use of inorganic phosphate (Pi) and dissolved organic phosphorus (DOP) by different bacterial groups was studied in experimental mesocosms of P‐starved eastern Mediterranean waters in the absence (control mesocosms) and presence of additional Pi (P‐amended mesocosms). The low Pi turnover times in the control mesocosms and the increase in heterotrophic prokaryotic abundance and production upon Pi addition confirmed that the bacterial community was originally P‐limited. The bacterioplankton groups taking up Pi and DOP were identified by means of microautoradiography combined with catalysed reporter deposition fluorescence in situ hybridization. Incubations with leucine were also performed for comparative purposes. All the probe‐identified groups showed a high percentage of cells taking up Pi and DOP in the control, P‐limited, mesocosms throughout the experiment. However, in response to Pi addition two contrasting scenarios in Pi use were observed: (i) on day 1 of the experiment Pi addition caused a clear reduction in the percentage of SAR11 cells taking up Pi, whereas Gammaproteobacteria , Roseobacter and Bacteroidetes showed similar percentages to the ones in the control mesocosms and (ii) on day 4 of the experiment, probably when the bacterial community had fully responded to the P input, all the probe‐identified groups showed low percentages of cells taking up the substrate as compared with the control mesocosms. These differences are likely related to different P requirements among the bacterial groups and point out to the existence of two contrasting strategies in P use.

Organic carbon and mineral nutrient limitation of oxygen consumption, bacterial growth and efficiency in the Norwegian Sea - L. Antonio Cuevas; Jorun K. Egge; T. Frede Thingstad; Birte Töpper (Polar Biology, 2011)

Bacterial community composition in an Arctic phytoplankton mesocosm bloom: the impact of silicate and glucose - Birte Töpper; Aud Larsen; Tron Frede Thingstad; Runar Thyrhaug; Ruth-Anne Sandaa (Polar Biology, 2010)

Viral control of bacterial biodiversity – evidence from a nutrient‐enriched marine mesocosm experiment - Ruth‐Anne Sandaa; Laura Gómez‐Consarnau; Jarone Pinhassi; Lasse Riemann; Andrea Malits; Markus G. Weinbauer; Josep M. Gasol; T. Frede Thingstad (Environmental Microbiology, 2009)
Summary We demonstrate here results showing that bottom‐up and top‐down control mechanisms can operate simultaneously and in concert in marine microbial food webs, controlling prokaryote diversity by a combination of viral lysis and substrate limitation. Models in microbial ecology predict that a shift in the type of bacterial growth rate limitation is expected to have a major effect on species composition within the community of bacterial hosts, with a subsequent shift in the composition of the viral community. Only moderate effects would, however, be expected in the absolute number of coexisting virus–host pairs. We investigated these relationships in nutrient‐manipulated systems, under simulated in situ conditions. There was a strong correlation in the clustering of the viral and bacterial community data supporting the existence of an important link between the bacterial and viral communities. As predicted, the total number of viral populations was the same in all treatments, while the composition of the viral community varied. Our results support the theoretical prediction that there is one control mechanism for the number of niches for coexisting virus–host pairs (top‐down control), and another mechanism that controls which virus–host pairs occupy these niches (bottom‐up control).

Algal—bacterial competition for phosphorus from dissolved DNA, ATP, and orthophosphate in a mesocosm experiment - Trond Løvdal; Tsuneo Tanaka; T. Frede Thingstad (Limnology and Oceanography, 2007)
We measured the turnover of phosphorus (P) from radioactive‐labeled dissolved deoxyribonucleic acid (dDNA), adenosine triphosphate (ATP), and orthophosphate, and the partitioning of P from these sources into different size fractions of algae and bacteria in nutrient‐manipulated mesocosms. There was a transition from uptake dominated by larger organisms during balanced enrichment toward uptake dominated by smaller organisms during nitrogen (N) enrichment (P starvation). Contrary to expectation, this effect was counteracted by glucose enrichment, probably because bacterial cells increased in size in a glucose‐amended mesocosm. During P starvation, estimates of biomass‐specific affinity for all substrates were consistent with uptake becoming limited by molecular diffusion transport toward the cells. Dissolved organic phosphorus (DOP) turnover times ( T ) fell to ~5 min for ATP and ~1.5 h for dDNA (compared to 1.1 and 15.6 h, respectively, during balanced enrichment), coincided with little inorganic P liberated from DOP in the water, and reflected a tight coupling between hydrolysis and uptake in this situation. At one time during the experiment, the ability of algae and bacteria to compete for P was also assessed by the combination of isotope dilution experiments and affinity estimates. High affinity and low values of the term K + S n (the half saturation constant + the natural concentration of bioavailable substrate) when the 1‐0.2‐µm size fraction was compared to the >1‐µm size fraction for all substrates indicated bacterial supremacy while in competition for both inorganic and organic P. No significant shift in algal‐bacterial competition for DOP relative to dissolved inorganic phosphorus (DIP) was found.

Partitioning of organic production in marine plankton communities: The effects of inorganic nutrient ratios and community composition on new dissolved organic matter - Pascal Conan; Morten Søndergaard; Theis Kragh; Frede Thingstad; Mireille Pujo-Pay; Peter J. le B. Williams; Stiig Markager; Gustave Cauwet; Niels Henrik Borch; Dylan Evans; Bo Riemann (Limnology and Oceanography, 2007)
We investigated the partitioning of carbon, nitrogen, and phosphorus between particulate and dissolved production using 11‐m 3 marine mesocosms (bags) in a Norwegian fjord with a salinity of 28.3, a chlorophyll concentration of 0.6 µg L −1 , an even biomass among five algal groups, and nitrogen limitation as the initial conditions. The experiment lasted 21 days in August. Addition of silicate (+Si) resulted in diatom dominance, while a more diverse community was present in treatments with no added Si (‐Si). Addition of inorganic nutrients in a N: P gradient from 64 to 4 either conserved the initial N limitation or forced the plankton communities to P limitation. Per added limiting nutrient, the diatom‐dominated bags produced more particulate (POC) and dissolved organic carbon (DOC) than the other bags. However, the relative partitioning of net production to POC and DOC did not differ as a function of the plankton communities. Between 22% and 33% of the net production accumulated as new DOC. The higher values were found in the N‐limited bags. The production of new dissolved organic nitrogen (DON) was variable over time, and short periods of positive production were followed by removal (negative production). Between 6% and 22% of the assimilated N was recovered as new DON in the N‐replete bags, while the DON production was very low during N limitation. The community structure had no effects on nitrogen partitioning. Diatom dominance (+Si bags) resulted in P sequestration to particles and a constant low net production of dissolved organic phosphorus (DOP) across the nutrient gradient. The production of DOP was low in the P‐limited (‐Si) bags; however, with a surplus of inorganic P, most of the assimilated P (74% to 85%) was recovered as new DOP. The consequence was a huge range in stoichiometric ratios for newly produced dissolved organic matter (DOM). With N limitation, the C:N ratio of new DOM was from 40 to 100, but it was below 40 under N‐replete conditions. The C: P ratio of new DOM in the ‐Si bags traced the P availability, and values approached 500 in P‐deficient bags to values between 17 and 58 in the P‐replete bags. The C: P ratio of new DOM in the +Si bags was about 300 at all dosing regimes. Consequently, the range in N: P ratios was also large, with values from below 1 to about 30. Carbon‐rich DOM in oceans and coastal waters is not necessarily a function of a slow diagenetic “maturation’’ process but can be produced almost immediately. Both the nutrient regime and phytoplankton community composition affected the production and composition of new DOM in this experiment.

Specific affinity for phosphate uptake and specific alkaline phosphatase activity as diagnostic tools for detecting phosphorus-limited phytoplankton and bacteria - Tsuneo Tanaka; Peter Henriksen; Risto Lignell; Kalle Olli; Jukka Seppälä; Timo Tamminen; T. Frede Thingstad (Estuaries and Coasts, 2006)

Use of non‐limiting substrates to increase size; a generic strategy to simultaneously optimize uptake and minimize predation in pelagic osmotrophs? - T. Frede Thingstad; Lise Øvreås; Jorun K. Egge; Trond Løvdal; Mikal Heldal (Ecology Letters, 2005)
Coexistence of two organisms competing for the same nutrient is possible if one is an ‘uptake’, and the other a ‘predation defence’ specialist. In pelagic food webs this principle has been linked to cell size. Small osmotroph cells, with their high surface : volume ratio, have been argued to be uptake specialists, while larger osmotrophs avoiding the intense grazing pressure from small protozoan predators might represent ‘predation defence’ specialists. This may seem like an obligatory trade‐off situation that necessitates a choice of either being small or being large, and thus being potentially dominant in oligotrophic or in eutrophic environments, respectively. However, in a more precise form, the theory for nutrient diffusion states that it is the ‘surface : cell requirement of limiting element’ ratio, rather than the ‘surface : volume’ ratio, that is important. The distinction is crucial, since it opens up the possibility of there being life strategies that use a non‐limiting element to increase size. Hypothesized to maximize uptake and predator defence simultaneously, such strategies should be particularly successful. We suggest that this strategy is exploited by osmotrophs with different size and physiology, such as heterotrophic bacteria, unicellular cyanobacteria and diatoms. Since the strategy implies a shift in organism stoichiometry, the biogeochemical implications are strong, illustrating the tight relationships between physical micro‐scale processes, organism life strategies, biodiversity, food web structure, and biogeochemistry.

Orthophosphate uptake by heterotrophic bacteria, cyanobacteria, and autotrophic nanoflagellates in Villefranche Bay, northwestern Mediterranean: Vertical, seasonal, and short‐term variations of the competitive relationship for phosphorus - Tsuneo Tanaka; Fereidoun Rassoulzadegan; T. Frede Thingstad (Limnology and Oceanography, 2004)
Previous studies have suggested that Mediterranean surface water becomes phosphorus limited for both bacteria and phytoplankton during stratified periods and that orthophosphate uptake in these situations was close to diffusion limitation for both cyanobacteria and autotrophic nanoflagellates. In order to better understand vertical and seasonal variations of this system, we measured orthophosphate uptake by bacteria and phytoplankton in Villefranche Bay (northwestern Mediterranean) monthly for the 0–75‐m layer and weekly or biweekly at 10 m from June to December 2002. Turnover time of orthophosphate was relatively short ( 30 h) in the deeper layer during the stratified period and in the whole water column during the mixing period. Short‐term fluctuations in turnover time were repeatedly observed from the stratified through the mixing periods. The dominance of PO 4 uptake drastically shifted from both bacteria and cyanobacteria to cyanobacteria when there were slight increases in turnover time (1‐10 h). Compared to the theoretical maximum calculated for diffusion limitation, mean affinity constants at 10 m were similar for autotrophic nanoflagellates and greater for cyanobacteria in situations with turnover time

Measurements of phosphate affinity constants and phosphorus release rates from the microbial food web in Villefranche Bay, northwestern Mediterranean - Tsuneo Tanaka; Fereidoun Rassoulzadegan; T. Frede Thingstad (Limnology and Oceanography, 2003)
Using 32 >P, uptake and transfer of phosphorus in the microbial food web were studied in surface water from Villefranche Bay (northwestern Mediterranean) from September to December 2001. During the study, the thermocline gradually declined and vertical mixing started, leading to a transition from a nutrient‐depleted period to a nutrient‐replete period. Before vertical mixing started, the orthophosphate turnover time ranged from 1 to 5 h. Orthophosphate uptake was dominated by the 0.6–2 µm size fraction (mean, 70%), where the cyanobacteria biomass was dominant. The estimated affinity constants for bacteria, cyanobacteria, and autotrophic nanoflagellates ranged from 0.001 to 0.028, 0.047 to 0.103, and 0.002 to 0.032 L nmol P −1 h −1 during the period, with relatively short (> 5 h) orthophosphate turnover times. These results suggest that cyanobacteria were superior for orthophosphate uptake among osmotrophs. For cyanobacteria and autotrophic nanoflagellates, the mean affinity constants were almost at the theoretical maximum predicted by diffusion‐limited uptake. On the basis of a cold‐chase technique, release rates of dissolved 32 P from labeled particles were > 0.5% h −1 , which corresponds to a turnover time of the particulate fraction up to three orders of magnitude greater than that of orthophosphate. Although a net loss of 32 P occurred in the 0.2–0.6 and 0.6–2 µm fractions, a net increase in the 32 P release from bacteria during the study period.

Silicate and labile DOC interfere in structuring the microbial food web via algal—bacterial competition for mineral nutrients: Results of a mesocosm experiment - Harry Havskum; T. Frede Thingstad; Renate Scharek; Francesc Peters; Elisa Berdalet; M. Montserrat Sala; Miquel Alcaraz; Jan C. Bangsholt; Ulla Li Zweifel; Åke Hagström; Maite Perez; John R. Dolan (Limnology and Oceanography, 2003)
The effects of organic and inorganic nutrient enrichments on algal‐bacterial competition were investigated using mesocosms. Interactions were followed over 10 d in 12, 3−m 3 seawater mesocosms in the Isefjord, Denmark. Two sets of four mesocosms were given the same daily addition of “phytoplankton nutrients” (phosphate and nitrate) but received different amounts of glucose, and one set was kept in excess with respect to silicate. Four additional mesocosms served as controls and received either no additions, silicate alone, or glucose alone. In the mesocosm set where no silicate was added, enrichment with phytoplankton nutrients and glucose led to a replacement of diatoms, not by other algae, but by heterotrophic bacteria, mainly bacteria > 2 µ. In the mesocosm set where silicate was kept replete, diatoms competed successfully with bacteria for the uptake of mineral nutrients. Even in mesocosms enriched with high amounts of glucose, primary production increased throughout the experimental period, while bacterial production, after an initial increase, leveled off. In addition, turnover time of glucose increased in the silicate‐replete mesocosm set, consistent with the idea that bacterial consumption was hampered by diatoms competing successfully for phosphate and nitrate. The size and shape of different algal and bacterial groups in relation to nutrient uptake and grazer avoidance are discussed. Both accumulation and consumption of dissolved organic carbon could depend on the structure of the microbial food web.

Prokaryotic genetic diversity throughout the salinity gradient of a coastal solar saltern - Susana Benlloch; Arantxa López‐López; Emilio O. Casamayor; Lise Øvreås; Victoria Goddard; Frida Lise Daae; Gary Smerdon; Ramón Massana; Ian Joint; Frede Thingstad; Carlos Pedrós‐Alió; Francisco Rodríguez‐Valera (Environmental Microbiology, 2002)
Summary Bacterial and archaeal assemblages have been studied in a multipond solar saltern using a range of microbial ecology techniques by four laboratories simultaneously. These include 16S rDNA sequencing from both denaturing gradient gel electrophoresis (DGGE) and clone libraries, and culturing methods. Water samples from eight ponds were analysed, covering a salinity range from near sea water (4% salt) to saturated sodium chloride (37% salt; ponds called crystallizers). Clone libraries focused on ponds with salinity of 8%, 22% and 32%. Although different cloning strategies were able to retrieve the same type of dominant sequences, there were differing degrees of success with less abundant sequences. Thus, the use of two sets of primers recovered a higher number of phylotypes. Bacterial and archaeal isolates were, however, different from any of the retrieved environmental sequences. For Bacteria, most sequences in the 8% salt pond were related to organisms of marine origin. Thus, representatives of the alpha‐, beta‐, gamma‐ and epsilon‐subdivisions of Proteobacteria, the Cytophaga–Flavobacterium–Bacteroides group (CFB), high‐G+C Gram‐positive bacteria and cyanobacteria were found. In the 22% salt pond, alpha‐ and gamma‐Proteobacteria, cyanobacteria and CFB were the only groups found, and most of them were related to specialized halophilic bacteria. From the 32% salt pond, only CFB were found, and most of the sequences retrieved clustered with Salinibacter ruber , an extremely halophilic bacterium. A decrease in the richness of bacterial genera was therefore apparent along the gradient. Archaea behaved quite similarly. In the lowest salinity ponds, sequences were related to environmental clones of Marine Archaea Group III ( Thermoplasmales relatives) and to unclassified branches of Euryarchaeaota. In the 8%, 22% and 32% ponds, most of the clones were related to different cultured strains of Halobacteriaceae. Finally, most sequences from the crystallizers clustered with the uncultured square archaeon SPhT. Crenarchaeaota were not detected. Despite the fact that higher prokaryotic richness was apparent in the lower salinity ponds than in the crystallizers, the diversity index from clone libraries calculated according to Shannon and Weaver did not show this trend. This was because diversity in the crystallizers can be considered as ‘microdiversity’, the co‐existence of several closely related clones of Bacteria (the S. ruber cluster) and Archaea (the SPhT cluster). Regardless of the changes in abundance, both Bacteria and Archaea showed the same pattern; as salinity increased, the number of different clusters decreased, and only one cluster became dominant. Both clusters, however, showed a considerable degree of microdiversity. The meaning of such microdiversity remains to be determined.

Elements of a theory for the mechanisms controlling abundance, diversity, and biogeochemical role of lytic bacterial viruses in aquatic systems - T. Frede Thingstad (Limnology and Oceanography, 2000)
Mechanisms controlling virus abundance and partitioning of loss of bacterial production between viral lysis and protozoan predation are discussed within the framework of an idealized Lotka‐Volterra–type model. This combines nonselective protozoan predation with host‐selective viral lysis of bacteria. The analysis leads to a reciprocal relationship between bacterial diversity and viruses, in which coexistence of competing bacterial species is ensured by the presence of viruses that ‘kill the winner,’ whereas the differences in substrate affinity between the coexisting bacterial species determine viral abundance. The ability of the model to reproduce published observations, such as an approximate 1:10 ratio between bacterial and viral abundance, and the ability of viral lysis to account for 10–50% of bacterial loss are discussed.

P limitation of heterotrophic bacteria and phytoplankton in the northwest Mediterranean - T. Frede Thingstad; Ulla Li Zweifel; Fereidoun Rassoulzadegan (Limnology and Oceanography, 1998)
Surface‐water microbial populations were investigated in the northwest Mediterranean for possible indicators of phosphate deficiency and limitation. Low phosphorus availability was suggested by short turnover time (min. observed 0.68 h), high‐alkaline phosphatase activity ( V max = 28 nM hydrolyzed h −1 ), subsaturation of phosphate uptake (2.6–9% of V max ), and high‐pulse uptake capacity of added orthophosphate. Based on high pulse uptake capacity and subsaturated uptake in both the >1‐µm and in the 0.2–1‐µm size fractions, P deficiency is suggested for both phytoplankton and heterotrophic bacteria. P limitation of heterotrophic bacteria was also supported by fast positive responses after phosphate addition in both thymidine incorporation in whole‐water samples and increased bacterial cell numbers in predator‐free water. No effects were found after addition of carbon or nitrogen sources alone. Combined with other published evidence, we suggest that the growth rates of not only phytoplankton, but also of heterotrophic bacteria, are P limited in this environment in summer. The finding has important implications for the dynamics of accumulation of dissolved organic carbon in the photic zone and thus for the carbon cycle of oceans.

Accumulation of degradable DOC in surface waters: Is it caused by a malfunctioning microbialloop? - T. Frede Thingstad; Åke HagstrÖm; Fereidoun Rassoulzadegan (Limnology and Oceanography, 1997)
Recent literature indicates that dissolved organic carbon (DOC) may accumulate in productive surface waters. Such accumulation will allow export of DOC to the aphotic zone by diffusion and downwelling. As an alternative to models based on low degradability, we here propose a mechanism where bacterial carbon consumption is restricted due to food web mechanisms controlling both growth and biomass of the bacteria: growth rate is kept low by bacteria‐phytoplankton competition for mineral nutrients, and biomass is kept low by bacterial predators. With such a mechanism, otherwise degradable material may accumulate and become subject both to chemical transformation and vertical transport. The steady‐states of a model describing the interactions between heterotrophic bacteria, phytoplankton, and bacterivorous protozoa is used to explore how the balance between DOC production and consumption shifts along a gradient from oligotrophy to eutrophy.

A theoretical approach to structuring mechanisms in the pelagic food web - T. Frede Thingstad (Hydrobiologia, 1997)